Further contribution to the knowledge of Ityphilus calinus Chamberlin, 1957, a poorly known ballophilid centipede from Colombia, with description of Ityphilus bonatoi, a new diminutive geophilomorph species from Brazil (Myriapoda: Chilopoda, Geophilomorpha) - Pereira, Luis Alberto (Zootaxa, 2013)
Ityphilus calinus Chamberlin, 1957 (Chilopoda: Geophilomorpha, Ballophilidae), a poorly known centipede from Cauca Valley, Colombia, is herein redescribed and illustrated after the male holotype, revealing the condition of the forcipular tarsungulum (which is completely smooth), also giving new data on many other morphological features of specific value until now unknown. A new diminutive species named Ityphilus bonatoi sp. nov. is herein proposed after the holotype female from Rio de Janeiro State, Brazil. The new species is characterized by having the internal edge of the forcipular tarsungulum serrate; among the other Neotropical members of the genus having the same trait, it only shares with I. donatellae Pereira, 2012 (from Central Amazon) a very small body size and a low number of leg-bearing segments. The new species represents the first record of the genus Ityphilus from the Atlantic Rainforest biome, and the southernmost representative of the genus in the Continent. A key for identification of the Neotropical species currently included in Ityphilus is also given.